2016
DOI: 10.1177/0165551515621838
|View full text |Cite
|
Sign up to set email alerts
|

Students’ collaborative inquiry – Relation to approaches to studying and instructional intervention

Abstract: In order to develop suitable pedagogical methods for inquiry based learning we need an increased understanding of factors that influence students' work in inquiry assignments. The aim of this study was to investigate how high school students' ways to work in a collaborative source-based writing assignment was influenced by their individual approach to studying and the teacher's instructions and guidance in the class. The respondents were 53 high school students who filled out a questionnaire regarding their wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…A growing number of teaching interventions are being carried out to improve information literacy knowledge and skills among students in elementary (e.g., Chen et al, 2017;Chu et al, 2011) and secondary schools (e.g., Alamettälä and Sormunen, 2020;Argelagós and Pifarré, 2012;Baji et al, 2018) using inquiry-based learning models. Inquiry-based frameworks such as guided inquiry have been integrated into schools' curricula (e.g., Heinström andSormunen, 2019, Kuhlthau et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing number of teaching interventions are being carried out to improve information literacy knowledge and skills among students in elementary (e.g., Chen et al, 2017;Chu et al, 2011) and secondary schools (e.g., Alamettälä and Sormunen, 2020;Argelagós and Pifarré, 2012;Baji et al, 2018) using inquiry-based learning models. Inquiry-based frameworks such as guided inquiry have been integrated into schools' curricula (e.g., Heinström andSormunen, 2019, Kuhlthau et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both Limberg (1999) and Heinström and Sormunen (2015) have examined the different ways information is used during research assignments. Lundh and Limberg (2012) have also examined the different ways pictures are used.…”
Section: Jd 756mentioning
confidence: 99%
“…These tables do not include the subjective characteristics of tasks identified by Kim and Soergel (2006) and Li and Belkin (2008) as these characteristics are connected to the search task doer not the search task itself. However, this distinction is important, particularly in the primary school IUE where the same objective task is assigned to a class but experienced differently by each class member (Limberg, 1999;Heinström and Sormunen, 2015). Future work could usefully establish all the subjective characteristics as they occur in primary schools, and the similarities and differences with other IUE.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The library can also support the strengths-based initiative at GSM is in modules where there is a strong and articulate research skills component and inquiry-based learning. Independent inquiry into conflicting viewpoints and alternative information sources is often in contrast with traditional assessment techniques which centre around “right answers” (Heinström and Sormunen, 2016, p. 325). Strategic students approach their learning process more through achievement-orientation than intrinsic motivation.…”
Section: Research Skills Training and Inquiry-based Learningmentioning
confidence: 99%
“…They typically orient towards the final grade, instead of the ongoing process of inquiry. They may therefore focus less on learning about the subject area in source-based assignments and pay particular attention to project-specific elements in their ambition to gain a good grade (Heinström and Sormunen, 2016). Ryan’s (2013) study revealed that students learn most in the early stages of a creative task (such as the video-based assessment), not from the final mark.…”
Section: Research Skills Training and Inquiry-based Learningmentioning
confidence: 99%